2016
DOI: 10.1186/s12931-016-0481-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for harm reduction in COPD smokers who switch to electronic cigarettes

Abstract: BackgroundElectronic cigarettes (ECs) are battery-operated devices designed to vaporise nicotine, which may help smokers quitting or reducing their tobacco consumption. There is a lack of data on the health effects of EC use among smokers with COPD and whether regular use results in improvement in subjective and objective COPD outcomes.We investigated long-term changes in objective and subjective respiratory outcomes in smokers with a diagnosis of COPD who quit or reduced substantially their tobacco consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 46 publications
6
96
0
4
Order By: Relevance
“…Although there is some evidence for lower annual exacerbation rates in smokers who switch to electronic cigarettes [47], there is also evidence that electronic cigarettes may have significant pulmonary toxicity [48]. Therefore, some organisations have suggested caution in using electronic cigarettes as a form of nicotine replacement therapy until further data are available [49].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Although there is some evidence for lower annual exacerbation rates in smokers who switch to electronic cigarettes [47], there is also evidence that electronic cigarettes may have significant pulmonary toxicity [48]. Therefore, some organisations have suggested caution in using electronic cigarettes as a form of nicotine replacement therapy until further data are available [49].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…8 This study demonstrated that these patients had a reduction in the frequency of acute exacerbations over 12 month and 24 month periods. In addition, dual users who reduced the amount of conventional tobacco cigarette smoking also had a reduction in the frequency of acute exacerbations.…”
Section: E-cigarettes and Lung Functionmentioning
confidence: 66%
“…In addition, dual users who reduced the amount of conventional tobacco cigarette smoking also had a reduction in the frequency of acute exacerbations. 8 To date, there is no information on the long-term effects of e-cigarettes on lung function in never smokers who adopt exclusive e-cigarette use. There is limited information in patients with lung disease, such as asthma or COPD.…”
Section: E-cigarettes and Lung Functionmentioning
confidence: 99%
“…A meta-analysis evaluating 7,332 patients with COPD reported that the combination of cognitive behavioural therapy (CBT) and nicotine replacement therapy was [34]. Electronic cigarette products are becoming increasingly popular [35]. However, their efficacy and safety are not well defined and thus their widespread use is not advocated [12].…”
Section: Smoking Cessationmentioning
confidence: 99%